ANALISIS KESIAPAN BELAJAR DARING SISWA KELAS VII PADA MASA PANDEMI COVID-19 DI DESA SIMPANG TIGA LAEBINGKE KECAMATAN SIRANDORUNG - Holong Sumurung Siagian; Tamin Ritonga; Roslian Lubis (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2021)
The aim of this study is to describe students’ readiness in learning online at seventh grade students in Simpang Tiga Laebingke, Sirandorung sub-district. The approach of the research used qualitative descriptive. Triangulation was used in checking data validity by using questionnaire (Guttman scale), observation, and interview (for students and Mathematics teacher) in collecting the data. The result of the research shows 1) based on questionnaire shows the average of students’ readiness in learning online is 65.33 (poor category), 2) based on interview shows the students have poor category students’ readiness in learning online , and 3) based on observation shows the students have poor category students’ readiness in learning online.